Tragedy, History, and the Form of Philosophy in Either/Or (Konturen, 2015)
Kierkegaard’s essay “The Tragic in Ancient Drama Reflected in the Tragic in Modern Drama,” makes two basic claims of far-reaching consequences for the theory of the tragedy and for philosophy more generally. The first is the claim that the essence of tragedy in all its historical manifestations consists in the representation of an irreducible contradiction between two qualitatively distinct principles: substantial determinants and individual agency. The second is Kierkegaard’s contention that, within this essence, the difference between the genre’s ancient and its modern forms rests on the different relations to that contradiction, on whether it is accepted as an objective fact or as a reflexive possibility. In the present article I elucidate Kierkegaard’s argument in terms of these two claims and point to some of their larger implications. With respect to the first, I show that it introduces a significant challenge to the conception of historical time on which our category of modernity depends. As concerns the second, I argue that it constitutes an engagement with what Kant calls as the modality of judgments (whether an object is possible, actual, or necessary), which Kierkegaard here attacks in the version given to it by the young F.W.J. Schelling. Kierkegaard’s rejection of Schelling’s argument on this point goes to the heart of the idealist project and ultimately questions what the form of philosophy should be.